Dass scores among students of allied health sciences at IIUM - Ahmad, Norsham; Ahmad Faris, Ain Nadzirah (IIUM Press, 2023)
Introduction: Depression, anxiety, and stress disorders are prevalent among university students, with healthcare students being more susceptible. The challenges specific to their field contribute significantly to the overall burden of mental health issues. As these students progress through clinical training, their predisposition to mental health issues increases, making it critical to address their well-being proactively. Aim: The purpose of this study was to explore the mental health conditions of allied health sciences students, and to compare the differences in Depression Anxiety Stress Scale (DASS)-21 scores between gender, year of study, and different departments among Kulliyyah of Allied Health Sciences (KAHS) students. Methodology: This was a cross-sectional questionnaire-based study conducted at the International Islamic University Malaysia (IIUM) Kuantan Campus. The completed DASS-21 questionnaire has been completed for a total of 534 allied health sciences students from six different departments at KAHS. Results: The prevalence of depression, anxiety and stress among allied health sciences students using DASS-21 was found to be 47%, 65.5%, and 33.3%, respectively. There were no significant differences in DASS-21 scores between gender and year of study. A statistically significant difference in DASS-21 scores between departments was found for symptoms of depression and anxiety. Conclusion: The student's mental health issues are concerning, with a significant level of severe anxiety reflecting psychological disorders among university students. Hence, the university should be aware of this and provide necessary aid for the student's mental well-being.